2020
DOI: 10.1111/ijfs.14865
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and in vitro digestibility of flours and starches from taro cultivated in different regions of Thailand

Abstract: This research aimed to study physicochemical properties and in vitro digestibility of flours and starches from taro cultivated in different regions of Thailand, that is, Kanchanaburi (KB), Chiang Mai (CM), Phetchaburi (PB) and Saraburi (SB). Taro starches were extracted from taro flours using either water or alkaline extraction. The taro flours had significantly (P ≤ 0.05) larger particle size, higher pasting and gelatinisation temperatures, and resistant starch content but lower total starch content, whitenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
(34 reference statements)
2
5
0
Order By: Relevance
“…These dimensions and appearance are similar to those reported by other authors in taro flours from Cuba (2.7 µm on average) [13] and Peru (0.3-10.0 µm) [51]. Wongsagonsup, et al [9] found much larger granule sizes in taro flours from Thailand, ranging from 52.17 to 67.63 µm, and indicated that this might be consequence of aggregated starch, because by isolating the starch, granule sizes ranged from 2.14-3.59 µm. At the bottom of the micrograph, other non-granular structures were clearly observed, which are attributed to other flour compounds.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 90%
See 3 more Smart Citations
“…These dimensions and appearance are similar to those reported by other authors in taro flours from Cuba (2.7 µm on average) [13] and Peru (0.3-10.0 µm) [51]. Wongsagonsup, et al [9] found much larger granule sizes in taro flours from Thailand, ranging from 52.17 to 67.63 µm, and indicated that this might be consequence of aggregated starch, because by isolating the starch, granule sizes ranged from 2.14-3.59 µm. At the bottom of the micrograph, other non-granular structures were clearly observed, which are attributed to other flour compounds.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 90%
“…Tarwi flour showed a marked lower starch content which was high compared with the value (1.3%) reported by Villacrés, et al [26] in debittered lupino. The starch content of taro in the present work was similar to that of taro from the Kanchannaburi (region of Thailand) and lower (59.8-72.62%) than that of some other varieties from several regions (Chiang Mai, Phetchaburi and Saraburi) in Thailand, attributing the drop in starch content to the decrease in average rainfall in the area [9]. The starch values in the present work are rather higher to those reported by Moorthy, et al [43] in fresh tubers of arracacha (20%) of taro (10-18%), camote (12-30%) and oca (12%) from Andean regions of Peru; these authors mentioned that the values could be associated with genotypic characteristics, climatic and environmental factors and the state of maturation.…”
Section: Moisturesupporting
confidence: 78%
See 2 more Smart Citations
“…I. batatas starches were either C-or A-type starch. [21][22][23] These starch granules have also been found to be polygonal in shapes, with generally bigger sizes compared to edible aroids like C. esculenta and Xanthosoma spp.…”
Section: Microstructure Structure and Molecular Characteristics Of Rtsmentioning
confidence: 99%